ANALISIS PENTINGNYA KOMPETENSI SOSIAL GURU TERHADAP PENDIDIKAN KARAKTER PADA MATA PELAJARAN IPS DI SDN 1 MOYOKETEN KECAMATAN BOYOLANGU KABUPATEN TULUNGAGUNG TAHUN AJARAN 2017/2018 - Mei Agustina Sintawati (Jurnal Bidang Pendidikan Dasar, 2018)
Teachers are required to master various competencies in carrying out the task of becoming a good educator. Educational institutions have a responsibility to instill character education through the learning process. This study aims to describe and analyze: (1) teacher's social competence in SDN 1 Moyoketen (2) character education at SDN 1 Moyoketen (3) teacher's social competence on character education at SDN 1 Moyoketen. This type of research is descriptive qualitative. Methods of data collection using questionnaires, interviews, field notes and documentation. The results showed that the social competence of third grade teacher of SDN 1 Moyoketen was very good with the questionnaire which showed the percentage of 89.17%. The value of character education of students is very good with the questionnaire which shows the percentage of 87.92%. It can be concluded that the social competence of third grade teacher of SDN 1 Moyoketen is very good, character education of third grade students of SDN 1 Moyoketen is very good, and teacher's social competence is very important in forming the value of character education of students.